MENJADI GURU ADALAH PENGABDIAN - Pujieni (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
Excellence and high performance with a sense of responsibilitycharacterize professional teachers. With professional competence, teachers willappear as counselors, coaches and learning managers who are able to interactwith students in the process of transferring knowledge, skills and values. Thepassion for learning not just teaching will help to upgrade knowledge, so itcan tackle the advancement of science and technology, as well as its utilizationopportunities to advance the teaching and learning process in the classroom.Improvement of teacher quality and competence is done continuously to renewitself according to the demands of the times. Moreover, the teacher must lovehis profession. The love of the profession is the entrance for teachers to becomeprofessional and qualified. Like her loving girl, she is willing to do anythingfor the girl she loves. If the teacher loves his profession, loves his students,whatever obstacles and difficulties encountered let alone only a low salaryor circumcision allowance will not be able to discourage teachers to work tohumanize young people.